Effects of dibutyryl cyclic adenosine monophosphate (dbcAMP) on growth and survival of buffalo oocytes - Mamun, S A; Islam, M A; Alam, M H; Moniruzzaman, M (Bangladesh Journal of Animal Science, 2025)
The function of cyclic adenosine monophosphate (cAMP) is to maintain the meiotic arrest in mammalian oocytes. This study was undertaken to determine the effects of dibutyryl cyclic Adenosine 3’,5’ -monophosphate (dbcAMP) on in vitro growth and survival of buffalo oocytes. Cumulus-oocyte-complexes (COCs) collected from early antral follicles were cultured for 14 days in growth culture medium dulbecco’s minimum essential medium supplemented with 0, 0.5, 2.5-, and 10-mM level of dbcAMP on collagen gel in 96-well culture plate at 38.5°C under an atmosphere of 5% CO2 in air. After 14 days 14.7, 5.9 and 5.9% oocytes become denuded; 67.6, 85.3 and 82.4% remained enclosed and 5.9, 5.9 and 5.9% were degenerated in 0.5, 2.5 and 10.0 mM dbcAMP supplemented culture, respectively. All oocytes were denuded in dbcAMP free group. After 14 days of culture 29.4, 52.9 and 41.2% oocytes increased over 116 μm; 44.1, 29.4 and 41.2% oocytes increased diameters between 100 to 115 μm and 14.7, 5.9 and 5.6% oocytes remain below 100 μm for 0.5, 2.5 and 10 mM dbcAMP supplemented culture respectively. After maturation 83.3, 50, 30.3 and 37.5% oocytes remain Germinal Vesicle (GV) stage and 16.7, 50, 67.6 and 68.8% oocytes went to meiosis I (MI) stage for 0, 0.5, 2.5 and 10 mM dbcAMP supplemented culture respectively, but none of them developed to the Meiosis II (MII) stage. Moreover In vivo grown oocytes were developed 37.5% to MII stage. The results showed that dbcAMP were maintained the integrity of oocytes and surrounding cumulus cells. In conclusion, during buffalo oocyte IVM the dbcAMP prevents denudation and degeneration of oocytes and increases survivability in culture by maintaining the meiotic arrest of oocytes and also increases the diameter of oocytes. Bangladesh Journal of Animal Science 54 (2): 54-65, 2025